The Savvy Survey #11: Mail-Based Surveys - Glenn D. Israel; Jessica L. Gouldthorpe (EDIS)
As part of the Savvy Survey Series, this publication provides Extension faculty with an overview of the process that uses mail for sending and receiving questionnaires. Mail surveys can be an effective way to collect data for needs assessments in program planning or for follow-up surveys evaluating outcomes of Extension programs. Survey research consistently shows that mail surveys usually obtain as high or higher response rates than other methods. This fact sheet provides guidance for constructing the questionnaire, addressing visual design and formatting considerations, and implementing the survey. Extension faculty who incorporate best practices of questionnaire design and mail survey procedures will be able to achieve a high response rate and collect more useful data than those who don’t use these best practices. This 9-page fact sheet was written by Glenn D. Israel and Jessica L. Gouldthorpe, and published by the UF Department of Agricultural Education and Communication, October 2013.